A LITERATURE REVIEW OF THE USE OF YOUTUBE TO MOTIVATE STUDENTS IN LEARNING ENGLISH - Alyssa Keysha Putri; Inayah Putri Nugroho; Aldriani Anditirta; Hery Nuraini (PRIMACY Journal of English Education and Literacy, 2024)
YouTube is an online media platform containing a variety of videos. It is also a place to post, share, and download videos.Its users range from children, teenagers, adults to parents, and no exception including students. This study aims to investigate the effect of using YouTube on students’ motivation in learning English. A qualitative method was used in this study, its study literature review. This research used descriptive research design to process the data and to draw the conclusions. Researcher gathered data from collecting literature to describe the situation related to the use of Youtube to motivate students in learning English. The result of this study was found out the implementation of YouTube videos in learning English was showed a positive impact on students to be more motivated.